Urban green space: creating a triple win for environmental sustainability, health, and health equity through behavior change - Kruize, H. (2020)
Urbanization, costs of green space maintenance, and diminishing connection between people and nature all exert pressures on urban green space. This is regrettable as green space has the potential to create wins for environmental sustainability, health, and health equity. This paper explores this potential triple win and investigates how to increase the use of urban green space through behavior change. A narrative literature review was conducted and was supplemented with literature suggested by experts. Results show that creating well-designed green spaces and stimulating people to use them can indeed deliver this triple win. Providing accessible, attractive, well-maintained green space with room for socialization, and where people feel safe, may increase the opportunity and motivation of people to use it more often. Informing and educating people and organizing activities may increase capability (and motivation) to use green space. Since the use of green space depends on life stage, lifestyle factors and individual values, it is important to involve potential users in its design. We recommend a specific focus on those groups who may benefit most from the use of green space. More evaluation is needed to inform effective green space interventions and to assess related economic, social, and environmental benefits.